2020
DOI: 10.34172/jept.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric upper gastrointestinal bleeding in children: etiology and treatment approaches

Abstract: Objective: Upper gastrointestinal bleeding (UGB) is one of the most important and serious cause of emergency admission in childhood. The aim of the study was to evaluate the etiological factors and the treatment approaches in patients with UGB. Methods: In this retrospective study, children with UGB admitted to emergency clinics of Istanbul Health Sciences University Kanuni Sultan Suleyman Research and Training Hospital, Istanbul Bakirkoy Sadi Konuk Research and Training Hospital and Diyarbakir Children’s Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…reported upper gastrointestinal tract bleeding to be more common than lower gastrointestinal tract bleeding and a combination of both (63.6%, 20.7%, and 15.6%, respectively). 11 Similar findings were also reported in Iran and Turkey. 12,13 Interestingly, our univariate analysis identified several factors as statistically significant risk factors for gastrointestinal bleeding in children with biliary atresia, such as liver cirrhosis, splenomegaly, thrombocytopenia, portal hypertension, and esophageal varices.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…reported upper gastrointestinal tract bleeding to be more common than lower gastrointestinal tract bleeding and a combination of both (63.6%, 20.7%, and 15.6%, respectively). 11 Similar findings were also reported in Iran and Turkey. 12,13 Interestingly, our univariate analysis identified several factors as statistically significant risk factors for gastrointestinal bleeding in children with biliary atresia, such as liver cirrhosis, splenomegaly, thrombocytopenia, portal hypertension, and esophageal varices.…”
Section: Resultssupporting
confidence: 77%
“…10 On the other hand, a different study reported a notably lower incidence of esophageal varices (11.1%) among children with upper gastrointestinal bleeding. 11 The disparity in these findings could be attributed to differences in diagnostic procedures, patient selection, and variations in disease severity across the studied populations.…”
Section: Resultsmentioning
confidence: 97%